PENGARUH SUBSTITUSI TEPUNG UBI JALAR TERHADAP KUALITAS SUS KERING - Oktariani, Elza; Elida, Elida; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was based on the lack of utilization of local raw materials such as orange sweet potato flour in the processing of dry sus. Sweet potato orange was used to reduce dependence on flour. The purpose of this study was to analyze the effect of substitution of orange sweet potato flour as much as 20%, 40% and 60% on external quality (volume, shape and color), and internal quality (smell, texture and taste). The type of this research was pure experiments (true experiment) with randomized data design method used was primary data sourced from 5 expert panelists by proposing the organoleptic test format. Analyze data using ANAVA, if Fcount> Ftable then proceed with Duncan test. The results showed that there were significant effects on external quality (volume, shape and color) and internal (aroma, crisp texture and taste, except hollow texture).Keywords: Orange Sweet Potato Flour, Dry Sus, Quality